Analisis Sistem Penangkal Petir Dengan Metode Elektrostatis Pada Rumah Sakit Indriati Boyolali - Abdul Kodir Al Bahar; Andri Pebrianto; Sri Hartanto (Teknik Elektro Universtias Krisnadwipayana, 2025)
The external electrostatic lightning protection system is installed to preventing, avoiding, and reducing the dangers of lightning strikes in the Indriati Boyolali Hospital which is located on Jl. Boyolali-Semarang No. KM.02, Mojosongo, Kec. Boyolali, Kab. Boyolali, Central Java 57322. This study discusses how to analyze the building's need for lightning protection, analyze the area protected by lightning protection and analyze the existing grounding system. The study began with the collection of primary data which means conducting research directly in the field and secondary data which means collecting data by taking measurements using an earth tester and calculation formulas in accordance with applicable regulations. The results of the study at Indriati Boyolali Hospital according to the PIUPP standard obtained a value of 18, this is very necessary for lightning protection, according to the NFPA 780 standard obtained a value of 28, this is very necessary for lightning protection and according to the IEC 1024-1-1 standard the level of protection with an efficiency of 95% which is in class II, this is also very necessary for lightning protection. Analysis of the protected area is 53,066 m² with a protection angle of 48.93°. Analysis of the grounding system at points A and B result 5.09 Ω and point C 26.69 Ω when the three points are connected in parallel the result is 2.33 Ω below the standard which is ≤ 5 Ω.